PENGEMBANGAN SUMBER DAYA MANUSIA DI DINAS PARAWISATA KABUPATEN KUPANG - Apriyani Ireny Osman; Frans Gana; M.N.C.B Neolaka (The Indonesian Journal of Public Administration (IJPA), 2020)
Abstract, The development of human resources in the tourism service has not been adequate due to various aspects of the drivers and obstacles. This study aims to identify the aspects of the drivers and inhibitors of human resource development in the Kupang District Tourism Office. Research using qualitative descriptive methods. With interview and documentation data collection techniques. Data collected uses analytical content to classify human resource development and the driving and inhibiting aspects of human resource development. The results of this study the Tourism Office is trying to improve human resources for employees and destinations in Kupang Regency tourism.Key words: development, human resources, tourism Abstrak, Pengembangan sumber daya manusia di dinas pariwisata belum memadai karena berbagai aspek pendorong dan penghambat. Penelitian ini bertujuan untuk mengengtahui aspek-aspek pendorong dan penghambat pengembangan sumber daya manusia di Dinas Pariwisata Kabupaten Kupang. Penelitian menggunakan metode deskriptif kualitatif. Dengan teknik pengumpulan data wawancara dan dokumentasi. Data terkumpul menggunakan konten analisis untuk mengklasifikasi pengembangan sumber daya manusia dan aspek-aspek pendorong dan penghambat pengembangan sumber daya manusia. Hasil penelitian ini Dinas Pariwisata sedang berupaya untuk meningkatkan sumber daya manusia bagi para pegawai dan destinasi-destinasi yang ada di pariwisata Kabupaten Kupang.Kata kunci: pengembangan, sumber daya manusia, pariwisata